Normal Appearing Ischaemic Brain Tissue on CT and Outcome After Intravenous Alteplase - Mair, Grant; Wardlaw, Joanna M. (Frontiers in Radiology, 2022)
Background and Aims The visibility of ischaemic brain lesions on non-enhanced CT increases with time. Obviously hypoattenuating lesions likely represent infarction. Conversely, viable ischaemic brain lesions may be non-visible on CT. We tested whether patients with normal appearing ischaemic brain tissue (NAIBT) on their initial CT are identifiable, and if NAIBT yields better outcomes with alteplase. Methods With data from the Third International Stroke Trial (IST-3, a large randomised-controlled trial of intravenous alteplase for ischaemic stroke) we used receiver-operating characteristic analysis to find a baseline National Institutes of Health Stroke Scale (NIHSS) threshold for identifying patients who developed medium-large ischaemic lesions within 48 hours. From patients with baseline CT (acquired <6 hours from stroke onset), we used this NIHSS threshold for selection and tested whether favourable outcome after alteplase (six-month Oxford Handicap Score 0-2) differed between patients with NAIBT versus with those with visible lesions on baseline CT using binary logistic regression (controlled for age, NIHSS, time from stroke onset to CT). Results From 2961 patients (median age 81 years, median 2.6 hours from stroke onset, 1534 [51.8%] female, 1484 [50.1%] allocated alteplase), NIHSS>11 best identified those with medium-large ischaemic lesions (area under curve=0.79, sensitivity=72.3%, specificity=71.9%). In IST-3, 1404/2961 (47.4%) patients had baseline CT and NIHSS>11. Of these, 745/1404 (53.1%) had visible baseline ischaemic lesions, 659/1404 (46.9%) did not (NAIBT). Adjusted odds ratio for favourable outcome after alteplase was 1.54 (95% confidence interval, 1.01-2.36), p=0.045 among patients with NAIBT versus 1.61 (0.97-2.67), p=0.066 for patients with visible lesions, with no evidence of an alteplase-NAIBT interaction (p-value=0.895). Conclusions Patients with ischaemic stroke and NIHSS >11 commonly develop sizeable ischaemic brain lesions by 48 hours that may not be visible within 6 hours of stroke onset. Invisible ischaemic lesions may indicate tissue viability. In IST-3, patients with this clinical-radiological mismatch allocated to alteplase achieved more favourable outcome than those allocated to control.